Modelling and Experimental Study on Electrically Heating Garment to Enhance Personal Thermal Comfort. Issue 1 (March 2021) - Huang, Qingjun; Xing, Guanying; Yang, Fan; Shu, Weicheng; Ma, Jinlong; Luo, Xiaobing
Abstract: Electrically heating garment (EHG) is an effective protection for human in cold environment. In this study, we analysed the principal agents of heat transfer in EHG, and established a theoretical model including heat conduction, natural convection and radiation. To verify the model, the numerical simulations and experiments were compared, and showed a temperature discrepancy smaller than 0.3°C, which was acceptable in engineering design. Using numerical simulation, it is convenient to optimize the design parameters of EHG in different thermal conditions. For instance, to maintain the average temperature of skin within 32-34°C when people are in low metabolic activities, the power of heating elements should range from 73.1-110.7 W/m 2 under high heating gear or 10.8-48.5 W/m 2 under low heating gear. The more importance is that the calculation allows easy predesign of EHG. The effect of the arrangements of heating elements was studied, herein, the results of six arrangement patterns were presented. It is found that the most effective arrangement can raise the average temperature of skin under heating elements about 0.4-1.2°C than other cases.